Perbaikan Kualitas Nira Aren Menggunakan Beberapa Pengawet Alami - Ati Atul Quddus; Hari Hariadi (JAGROS : Jurnal Agroteknologi dan Sains (Journal of Agrotechnology Science), 2018)
Indonesia is one of the sugar producing countries in the world, but the domestic sugar industry is still unable to meet the needs of its own country. The condition of sugar self-sufficiency is pursued through the development of sugar cane and also through other sources of raw materials, one of which is from palm sugar. Palm juice quickly changes to acid because of the fermentation process, which is usually caused by late processing after tapping, or because of the uncleanness of the juice container. This study aims to observe the effect of giving natural preservatives in the form of hiris leaf powder, mangosteen peel powder, and palm sugar in maintaining the quality of palm juice done in several concentrations (b / v). The research method used was an experimental method with a method. The first factor was 3 levels of natural preservative types (mangosteen peel powder, sliced leaves, and brown sugar), while factor II was 3 preservative concentration levels (3%, 4.5%, and 6%), and each treatment was repeated 3 times so that it was obtained 27 trial units. The test results showed that the lowest reducing sugar content in palm sugar using natural preservatives was found in the Hiris Leaf with an average of 31.192% and 4.5 treatment dose with an average of 34.683%. While for the lowest moisture content found in palm sugar that uses natural preservatives of mangosteen peel with an average of 1.5983% and the best treatment dose is at dose 3 with an average of 1.1267% Keywords: hiris leaves, mangosteen peel, palm juice, natural preservatives